LINC00673 rs11655237 C>T confers neuroblastoma susceptibility in Chinese population. Issue 1 (8th February 2018) - Zhang, Zhuorong; Chang, Yitian; Jia, Wei; Zhang, Jiao; Zhang, Ruizhong; Zhu, Jinhong; Yang, Tianyou; Xia, Huimin; Zou, Yan; He, Jing
Abstract : Neuroblastoma, which accounts for approximately 10% of all pediatric cancer-related deaths, has become a therapeutic challenge and global burden attributed to poor outcomes and mortality rates of its high-risk form. Previous genome-wide association studies (GWASs) identified the LINC00673 rs11655237 C>T polymorphism to be associated with the susceptibility of several malignant tumors. However, the association between this polymorphism and neuroblastoma susceptibility is not clear. We genotyped LINC00673 rs11655237 C>T in 393 neuroblastoma patients in comparison with 812 age-, gender-, and ethnicity-matched healthy controls. We found a significant association between the LINC00673 rs11655237 C>T polymorphism and neuroblastoma risk (TT compared with CC: adjusted odds ratio (OR) =1.80, 95% confidence interval (CI) =1.06–3.06, P =0.029; TT/CT compared with CC: adjusted OR =1.31, 95% CI =1.02–1.67, P =0.033; and T compared with C: adjusted OR =1.29, 95% CI =1.06–1.58, P =0.013). Furthermore, stratified analysis indicated that the rs11655237 T allele carriers were associated with increased neuroblastoma risk for patients with tumor originating from the adrenal gland (adjusted OR =1.51, 95% CI =1.06–2.14, P =0.021) and International Neuroblastoma Staging System (INSS) stage IV disease (adjusted OR =1.60, 95% CI =1.12–2.30, P =0.011). In conclusion, we verified that the LINC00673 rs11655237 C>T polymorphism might be associated with neuroblastoma susceptibility. Prospective studies with a large sample size and different ethnicities are needed to validate our findings.